Analysis of Risk Factors for Low Birth Weight (LBW) in the Work Area of the Setu II Bekasi Health Center - Abela Mayunita; Nurkhotimah (Global Writing Academica Researching and Publishing, 2023)
The aim of the study was to analyze the risk factors for LBW events in the working area of the Setu II Bekasi Health Center in 2022. This research was an analytic survey study using a cross-sectional study design with a population of 521 people and a sample of 84 people who were selected using a random sampling technique. Data was taken using a questionnaire which was then processed using a statistical program. Results: The study found that 22.6% of babies were born with a weight < 2500 grams, 27.4% of mothers aged < 20 and > 35 years, 20.2% of mothers with gestational age < 37 weeks, 28.6% of mothers with parity ≥ 3 children, 14.3% of mothers had LILA <23.5 cm, 7.1% of mothers had HB levels <10 g/dl, 10.7% of mothers experienced pregnancy complications. The results of statistical analysis using the chi square test found that the risk factors associated with the incidence of LBW were gestational age (p value = 0.000), parity (p value = 0.019) and pregnancy complications (p value = 0.025). While the risk factors that were not related to the incidence of LBW were mother's age (p value = 0.179), upper arm circumference (p value = 0.455) and HB levels (p value = 0.126). Conclusion: the risk factors associated with the incidence of LBW are gestational age, parity and complications of pregnancy. Therefore, it is hoped that parents will always take care of their pregnancies by checking their pregnancies to health services, so as to minimize risk factors during pregnancy